Człowiek i jego życie słowem. W nawiązaniu do Prologu Ewangelii według św. Jana (tłum. P. Mikulska) - SALMERI, Giovanni; MIKULSKA, Patrycja (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
The Prologue to the Gospel according to John apperas to have no bearing on the foundations of philosophical ethics, especially within the Christian tradition that has so strongly emphasized the gap between theoretical discourse on the one hand, and the moral one on the other. However, the Prologue points to the crucial fact that the human being should be considered on the basis of their relationship to the word. In fact, most ethical precepts refer, directly or indirectly, to the word, which enables the emergence of otherwise inconceivable values. Different concepts of freedom may also be co-ordinated, if man is understood as a being focused on the word, and not primarily as a rational being. Translated by Patrycja Mikulska